Social egg freezing: Motivations, treatment experiences and the impact of Covid‐19 – a single‐center experience - Sughashini Murugesu; Mikaela Maria Charalambides; Benjamin P. Jones; Srdjan Saso; Raef Faris; Jaya Parikh; James Nicopoullos; Meen‐Yau Thum; Timothy Bracewell‐Milnes (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study aims to assess the motivations and treatment experiences of women undergoing social egg freezing and to understand the impact of the Covid‐19 pandemic. Material and methods Between January 2011 to December 2021, 191 social egg freezing patients were recruited from the Lister Fertility Clinic, London UK. Participants completed a validated questionnaire investigating patients’ perspectives of social egg freezing. A response rate of 46.6% was achieved. Results In all, 93.9% of women expressed concern regarding age‐related fertility decline which influenced their decision to undergo social egg freezing. The majority (89.5%) of women were not in a relationship at the time of social egg freezing and considered this a motivating factor. Also, 39.0% of participants had side effects related to treatment which affected work and social life. Participants were significantly more likely to experience side effects if they underwent multiple egg freezing cycles (χ2, p < 0.01) or if they cryopreserved oocytes during the COVID‐19 pandemic (χ2, p < 0.05). Of the women, 64.0% wished to have cryopreserved oocytes at a younger age, a view significantly more likely if older than 37 years at first social egg freezing cycle (χ2, p < 0.001). Also, 82.3% of women reported their decision to undergo social egg freezing was not delayed due to concerns regarding COVID‐19 exposure during treatment; 44.1% considered the pandemic made them more willing to undergo social egg freezing. Conclusions Most participants did not regret their decision to undergo social egg freezing but the majority wished they had cryopreserved oocytes at a younger age. This highlights the importance of early education to optimize outcomes and patient choice. The egg freezing process can be stressful, women may have concerns around social egg freezing and unprecedented situations such as the COVID‐19 pandemic may alter treatment experience.